2021
DOI: 10.5755/j01.erem.77.4.29942
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Shading Device and Semi-Circle Horizontal Light Pipe Transporter for High-Rise Office Building in Tropical Climate

Abstract: The blooming of a deep open plan in office buildings is accelerated due to economic profit reasons. This hinders the utilisation of daylight despite having abundance of daylight in tropical climate. Although a light pipe (LP) provides a means to illuminate the deep interior of the space, non-uniform daylight distribution still occurs due to the high illumination contrast across the room. The integration of a shading device (SD) in a room with an LP offers a solution to create a uniform daylight distribution. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…IOP Publishing doi:10.1088/1755-1315/1281/1/012056 2 A Horizontal Light Pipe (HLP) is an innovative daylighting system [8] that can distribute daylight into an area far from the side window. Considering the Tropics, the design significance is usually on avoiding overheating and glare by controlling the daylight level penetrating the building; HLP should be combined with shading systems [9,10]. In an office room with unilateral daylighting, combining HLP and shading systems can improve daylight performance inside the building by reducing the average daylight level and improving daylight uniformity [9].…”
Section: Introductionmentioning
confidence: 99%
“…IOP Publishing doi:10.1088/1755-1315/1281/1/012056 2 A Horizontal Light Pipe (HLP) is an innovative daylighting system [8] that can distribute daylight into an area far from the side window. Considering the Tropics, the design significance is usually on avoiding overheating and glare by controlling the daylight level penetrating the building; HLP should be combined with shading systems [9,10]. In an office room with unilateral daylighting, combining HLP and shading systems can improve daylight performance inside the building by reducing the average daylight level and improving daylight uniformity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that horizontal light pipe (LP) has the potential to transport daylight and illuminate the deep interior of such rooms [15][16][17][18]. Although vertical LP provides an alternative to distribute the daylight, it is not feasible to be applied in a high-rise building as it sacrifices valuable space for daylight transport from the rooftop to the floors below compared to horizontal LP which can be retrofitted at plenum spaces [14,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, although the deep interior can be illuminated up to 100-300 lx, there is still a high daylight penetration at the front portion of the room that receives more than 500 lx, and this causes visual discomfort [1]. According to the author's preliminary research, integrating shading devices with LP has the potential to attain a more uniform daylight distribution [15].…”
Section: Introductionmentioning
confidence: 99%
“…daylight can be transported into the deep interior by employing a light transport system such as a horizontal light pipe (LP) [10][11][12][13][14]. Though previous research had investigated the vertical LP usage [15][16][17], it is not feasible to use a vertical LP in a high-rise office building as it requires sacrificing valuable space for daylight transport from the rooftop to the floors below.…”
Section: Introductionmentioning
confidence: 99%
“…However, the daylight distribution in a room with horizontal LP has contrasting illumination level which will cause visual discomfort at both ends of the space where the front, middle, and rear portion of the room received above 500 lx, 300-500 lx, and 100-300 lx respectively. According to the author's preliminary research, integrating shading devices with LP has the potential to attain a more uniform daylight distribution [10].…”
Section: Introductionmentioning
confidence: 99%